SSD Failures in Datacenters: What, When and Why? - Narayanan, Iyswarya; Wang, Di; Jeon, Myeongjae; Sharma, Bikash; Caulfield, Laura; Sivasubramaniam, Anand; Cutler, Ben; Liu, Jie; Khessib, Badriddine; Vaid, Kushagra (SYSTOR, 2016)
Despite the growing popularity of Solid State Disks (SSDs) in the datacenter, little is known about their reliability characteristics in the field. The little knowledge is mainly vendor supplied, and such information cannot really help understand how SSD failures can manifest and impact the operation of production systems, in order to take appropriate remedial measures. Besides actual failure data and the symptoms exhibited by SSDs before failing, a detailed characterization effort requires wide set of data about factors influencing SSD failures, right from provisioning factors to the operational ones. This paper presents an extensive SSD failure characterization by analyzing a wide spectrum of data from over half a million SSDs that span multiple generations spread across several datacenters which host a wide spectrum of workloads over nearly 3 years. By studying the diverse set of design, provisioning and operational factors on failures, and their symptoms, our work provides the first comprehensive analysis of the what, when and why characteristics of SSD failures in production datacenters.
Best Student Paper Award